2012
DOI: 10.1159/000345943
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Neutrophil Recruitment into the Lung, Liver, and Kidney

Abstract: The recruitment of immune cells is crucial for the development of inflammatory processes. The classical recruitment cascade of neutrophils into inflamed tissues is well understood and consists of capturing, rolling, slow rolling, arrest, postadhesion strengthening, crawling, and transmigration. While this commonly agreed paradigm might be applicable to most peripheral tissues, recruitment mechanisms may substantially vary in different organs such as the lung, liver, and kidney. These organs are highly speciali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
79
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 89 publications
4
79
0
1
Order By: Relevance
“…These data are in contrast to a previous report that indicates that CD45 do not have a prominent function in neutrophil recruitment in a S. aureus airpouch model (12). These data support the hypothesis that the molecular mechanisms of neutrophil recruitment into different tissues differ (45). Another explanation for these controversial results is that different bacteria elicit distinctive signaling pathways (35).…”
Section: Discussionsupporting
confidence: 49%
“…These data are in contrast to a previous report that indicates that CD45 do not have a prominent function in neutrophil recruitment in a S. aureus airpouch model (12). These data support the hypothesis that the molecular mechanisms of neutrophil recruitment into different tissues differ (45). Another explanation for these controversial results is that different bacteria elicit distinctive signaling pathways (35).…”
Section: Discussionsupporting
confidence: 49%
“…the leukocytes leave the vessel and migrate into the inflamed tissue [14]. Recent studies demonstrated that leukocyte recruitment into the kidney occurs at two different sites [16]: Leukocyte rolling and recruitment in the postcapillary venules in the cortex are E-selectin-dependent [17], whereas glomerular inflammation results in an increase in the duration of retention of static and migrating leukocytes [18]. …”
Section: Introductionmentioning
confidence: 99%
“…Due to its unique microvasculature, the molecular mechanisms involved in neutrophil recruitment into the lung differ compared with other organs (51). Chemokine signaling plays a dominant role for neutrophil recruitment into the lung tissue, whereas selectins are only of minor importance in response to most inflammatory stimuli in the lung.…”
Section: Discussionmentioning
confidence: 99%